STRUCTURAL TYPES OF SENTENCES IN ENGLISH AND UZBEK LANGUAGES - Bereketova Nursipat Nurladinovna; Bafoyeva Nilufar Salimovna (PEDAGOGS, 2024)
Annotation: This article explores the structural types of sentences in English and Uzbek, emphasizing their differences and similarities. It begins by outlining the four main types of sentences in English: simple, compound, complex, and compound-complex. Each type is defined and illustrated with examples. The article then presents the corresponding sentence types in Uzbek, highlighting the parallel structures while noting the unique features of each language. Key differences, such as word order (SVO in English vs. SOV in Uzbek), use of conjunctions, and tendencies in sentence length and complexity, are discussed. The conclusion underscores the value of understanding these aspects for improved language learning and communication.